Synthesis and Anticancer Evaluation of New 1,3,4-Oxadiazole Derivatives - Camelia Elena Stecoza; George Mihai Nitulescu; Constantin Draghici; Miron Teodor Caproiu; Octavian Tudorel Olaru; Marinela Bostan; Mirela Mihaila (MDPI AG, 2021)
In order to develop novel chemotherapeutic agents with potent anticancer activities, a series of new 2,5-diaryl/heteroaryl-1,3,4-oxadiazoles were designed and synthesized. The structures of the new compounds were established using elemental analyses, IR and NMR spectral data. The compounds were evaluated for their anticancer potential on two standardized human cell lines, HT-29 (colon adenocarcinoma) and MDA-MB-231 (breast adenocarcinoma). Cytotoxicity was measured by MTS assay, while cell cycle arrest and apoptosis assays were conducted using a flow cytometer, the results showing that the cell line MDA-MB-231 is more sensitive to the compounds' action. The results of the predictive studies using the PASS application and the structural similarity analysis indicated STAT3 and miR-21 as the most probable pharmacological targets for the new compounds. The promising effect of compound 3e, 2-[2-(phenylsulfanylmethyl)phenyl]-5-(4-pyridyl)-1,3,4-oxadiazole, especially on the MDA-MB-231 cell line motivates future studies to improve the anticancer profile and to reduce the toxicological risks. It is worth noting that 3e produced a low toxic effect in the D. magna 24 h assay and the predictive studies on rat acute toxicity suggest a low degree of toxic risks.